A study on Flavoured milk consumption among 1AB School students in Jaffna Municipal Council Area - Guberan, G.; Sinniah, J.; Silva, K.F.S.T. (International Symposium on Agriculture and Environment, 2012)
This study was conducted to study the availability, consumption pattern, and factors limiting the flavoured milk consumption among Advance Level 1AB (schools which have science stream in the advance level) school students in the Jaffna Municipal Council area. The survey was carried out in May 2011 using a pre-tested questionnaire. Data was collected from ten schools and the sample comprised 331 students. Data was entered onto the computer and analyzed using SAS. The percentage of students consumed UHT (ultra heat treated) milk, pasteurized milk, and in-bottle sterilized milk were 73.41, 53.17, and 07.25, respectively. When the students from urban area and rural area were considered comparatively higher percentage of students from rural area (87.68) consumed flavoured milk than students from urban area (82.90). Flavoured milk consumption by female students (90.35%) was comparatively higher than the male students (76.86%). Flavoured milks consumed by the students with higher frequency of once a week which was followed by once in two day. Availability and accessibility (59.89%) of the flavoured milk was the major limiting factor, while price of flavoured milk, health reasons like throat phlegm, consumption of soft drinks, attractive packaging, perception on taste, and relative/friends’ preference also played an important role in determining the consumption pattern of flavoured milk. The study concluded that students had considerable willingness to increase the consumption of flavoured milk when the flavoured milks are easily available at local market with low price and high quality.
Keywords: Flavoued milk; Jaffna; Rural area; Students